Hand Grip Strength and nutritional status in hospitalized oncological patients - STEEMBURGO, Thais; AVERBUCH, Natália Cristina; Sanini BELIN, Christy Hannah; BEHLING, Estela Beatriz (Revista de Nutrição, 2023)
Objective To evaluate the nutritional status and functional capacity of hospitalized adult patients. Methods Cross-sectional study of adult oncology patients at Hospital de Clínicas de Porto Alegre. Patients were evaluated according to Solid Tumors and Hematologic Tumors. The nutritional status was obtained using Patient Generated Subjective Global Assessment, and the functional capacity was evaluated by Handgrip Strength using a Jamar® dynamometer – and the Performance Index of the Eastern Cooperative Oncology Group. Results This study evaluated 76 patients (56±17 years old, 35.5% female), 63.2% with Solid Tumors and 36.8% with Hematologic Tumors. According to the Patient Generated Subjective Global Assessment, 53.9% of the patients were moderately and severely malnourished and demonstrated functional capacity, according to the Handgrip Strength and Performance Index of the Eastern Cooperative Oncology Group, of 47.9% and 32.2%, respectively. The functional capacity instruments showed a moderate agreement (Kappa=0.427, p<0.001) and positive correlation (r=0.136, p=0.028). Severely malnourished patients had a lower Handgrip Strength when compared to well nourished (24.0±10.4 vs. 34.2±16.6kg, p=0.015). The results were confi rmed among moderately and severely malnourished patients, who were rated at the 40 percentile, considered low functional capacity. Conclusion In this study, hospitalized oncological patients presented poor nutritional status and low functional capacity. The Patient Generated Subjective Global Assessment identifies the nutritional specification earlier. In addition, Handgrip Strength dynamometry can be a useful tool to evaluate the low functional capacity and nutritional status. It can be included in cancer patient’s evaluation, along with other nutritional assessment tools.